Structural role of conserved Asn179 in the short-chain dehydrogenase/reductase scaffold. - Filling, C; Nordling, E; Benach, J; Berndt, K; Ladenstein, R; Jörnvall, H; Oppermann, U (2001)
Short-chain dehydrogenases/reductases (SDR) constitute a large family of enzymes found in all forms of life. Despite a low level of sequence identity, the three-dimensional structures determined display a nearly superimposable alpha/beta folding pattern. We identified a conserved asparagine residue located within strand betaF and analyzed its role in the short-chain dehydrogenase/reductase architecture. Mutagenetic replacement of Asn179 by Ala in bacterial 3beta/17beta-hydroxysteroid dehydrogenase yields a folded, but enzymatically inactive enzyme, which is significantly more resistant to denaturation by guanidinium hydrochloride. Crystallographic analysis of the wild-type enzyme at 1.2-A resolution reveals a hydrogen bonding network, including a buried and well-ordered water molecule connecting strands betaE to betaF, a common feature found in 16 of 21 known three-dimensional structures of the family. Based on these results, we hypothesize that in mammalian 11beta-hydroxysteroid dehydrogenase the essential Asn-linked glycosylation site, which corresponds to the conserved segment, displays similar structural features and has a central role to maintain the SDR scaffold.